Mudanças fisiológicas, morfológicas e comportamentais em Zabrotes subfasciatus (Boheman) (Coleoptera, Bruchidae) associadas ao consumo de diferentes variedades de feijão (Phaseolus vulgaris L.) - Marteleto, Patrícia Bonifácio (2007)
The phenotypic plasticity defines the organism ability to modify its physiology/morphology in response to the environmental conditions without major genetic changes (Scheiner). This study was developed in order to verify physiologic, morphologic and behavioral changes in two different Zabrotes subfasciatus (Boheman) (Coleoptera, Bruchidae) populations submitted to different diets of beans varieties (Phaseolus vulgaris L.) (Fabaceae). Female longevity (medium life time), fertility and preference for oviposition site, as well as size and levels of fluctuanting asymmetry (FA) were registered. There were observed physiologic and morphologic modification related to the diet used. Z. subfasciatus is a generalist specie, consuming and ovipositioning in different bean varieties. Its ability to use different resources is important to the population survivorship preventing it against extinction. The Hopkins principle that determines the influence of previous female experience in the choice of oviposition sites was not confirmed. The studied populations had different plastic responses for the same treatments, indicating genetic, physiology and behavioral variation on its plastic response. Males and females have different abilities to obstruct FA occurrence and this evidentiate the influence of genomic factors determining this character.